Pengembangan Aplikasi Jasa Cuci Sepatu Menggunakan Teknologi GPS Berbasis Android - Martin Setyawan Wibowo; Sutarman; Saucha Diwandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
The shoe cleaning service business provides professional services in shoe care and is a solution for the community. The development of the shoe industry is the cause of this business continuing to grow, making business actors have to create new innovations in promotional media and service processes to be able to compete. This research aims to develop an Android-based shoe washing service application using Android Studio with the Java programming language and Firebase as a database. This application applies Global Positioning System (GPS) technology to support shuttle services. The system development method used is the waterfall method with 5 stages, namely analysis, design, implementation, testing and maintenance. The results of this research are that the Android-based shoe washing service application can be used as expected, making it easier for business actors to manage orders and making it easier for customers to order by getting pick-up and drop-off services.